Balai Kerajaan Saksi-saksi Yehowa Mengenai Keselamatan Serta Kaitannya dengan Natal dan Allah Tri Tunggal - Rona Sumantri Lumbantungkup; Suardin Zega; Anita Lase; Mariska Sihite; Perlin Zebua (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Against the background of differences in understanding and views, both in matters of divinity, views of the Bible, and the rules of worship and celebration of major holidays. The understanding of the Kingdom Hall of Jehovah's Witnesses is different from the understanding of Protestant Christians in general, Jehovah's Witnesses do not recognize the concept of the Triune God, do not use the sign of the cross either in places of worship or for funerals. This study is based on the results of research conducted in the field with qualitative research and using a case study approach. Jehovah's Witnesses prioritize Easter celebrations over Christmas celebrations, because there are no verses in the holy book that encourage Christians to celebrate Christmas. Jehovah's Witnesses are a Christian denomination known for its unique interpretation of the Bible. They emphasized the importance of God's name, Jehovah, and rejected the doctrine of the Trinity or the concept of a Triune God. This community is also known for its door-to-door preaching activities and rejection of Christmas celebrations. This paper will discuss a brief history, core beliefs, and religious practices of Jehovah's Witnesses, as well as analyze their relationships with communities of other religious groups and society's views of these groups